Primary breast sarcoma: A case series - Manisha Ahuja; Varuna Mallya; Shramana Mandal; Reena Tomar; Radhika Aggarwal; Nita Khurana; Pawnindra Lal (Wolters Kluwer Medknow Publications, 2022)
Background: Primary Breast Sarcomas (PBS) are rare malignancies and seen in less than <1 % of all breast malignancies. PBS are non epithelial, composed of mesenchymal mammary tissue and are difficult to diagnose from other sarcomas arising in breast. Materials and Methods: A retrospective study was conducted in the Department of Pathology and slides of breast malignancies over a period of 5 years were reviewed. Out of total 1570 breast malignancies, 5 cases were reported as PBS. Diagnosis was made on the basis of Histopathology and IHC findings. Results: Out of total 1570 cases, 5 cases were diagnosed as PBS (i.e. 0.32% of all cases). 3 out of 5 cases were males comprising of 60% of cases and 2 cases were females accounting for 40% of cases. The age group of presentation was 32-65 years with mean age being 48.5 years. A diagnosis of MPNST was rendered in two cases ( 1=M, 1=F), one each was diagnosed as DFSP ( with fibrosarcoma), Leiomyosarcoma and Fibrosarcoma. Conclusion: PBS is an extremely rare entity and locally aggressive. It requires diagnosis as its treatment protocol is different.